2013
DOI: 10.2105/ajph.2012.300812
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biases Against Latinos and African Americans Among Primary Care Providers and Community Members

Abstract: Objectives This study assessed implicit and explicit bias against both Latinos and African Americans, among experienced primary care providers (PCPs) and community members (CMs) in the same geographic area. Methods 210 PCPs and 190 CMs from three health care organizations in the Denver metro area completed Implicit Association Tests and self-report measures of implicit and explicit bias, respectively. Results With a 60% participation rate, the PCPs demonstrated substantial implicit bias against both Latino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 28 publications
6
117
0
Order By: Relevance
“…Studies of unconscious bias in healthcare have focused largely on Black Americans, and while this focus should not be abandoned, the recent growth of non-Black racial/ethnic minorities (e.g., Latinos/as and Asians) in the US calls for broadening the lens on the problem of racial/ethnic discrimination in US health care. In addition, US research on discrimination in health care still focuses largely on race 8,29,33,44 (though studies focused on anti-Latino/a discrimination are slowly increasing 37 ) to the neglect of gender and social class. Available evidence 22 suggests that the gender of the physician can play an important role in clinical decision-making; so might the gender of the patient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of unconscious bias in healthcare have focused largely on Black Americans, and while this focus should not be abandoned, the recent growth of non-Black racial/ethnic minorities (e.g., Latinos/as and Asians) in the US calls for broadening the lens on the problem of racial/ethnic discrimination in US health care. In addition, US research on discrimination in health care still focuses largely on race 8,29,33,44 (though studies focused on anti-Latino/a discrimination are slowly increasing 37 ) to the neglect of gender and social class. Available evidence 22 suggests that the gender of the physician can play an important role in clinical decision-making; so might the gender of the patient.…”
Section: Resultsmentioning
confidence: 99%
“…Blair et al 37 Metropolitan Denver, Colorado. Unlike most other studies of physician implicit bias which tend to focus on medical residents, 30% of the PCPs in this study had between 11-20 years of clinical experience and 21% had more than 21 years of clinical experience.…”
Section: Physician Implicit Bias: Measurement Correlates and The Domentioning
confidence: 99%
“…[39][40][41][42][43] Investigations of clinicians' ethnic and racial attitudes have shown that, similar to the general population, clinicians show little explicit or intentional bias but exhibit substantial bias in their implicit (unconscious) attitudes. [44][45][46] Theoretical models suggest that clinicians' implicit bias may affect their delivery of health care in 3 ways. 42,47,48 First, implicit bias may directly influence clinicians' decisions about their patients' medical treatment, with incorrect, often stereotypical assumptions leading to lower-quality care for minority than for white patients.…”
Section: Race/ethnicity Racism and Cvdmentioning
confidence: 99%
“…Several studies [52][53][54] have found associations between clinicians' implicit bias and worse clinical interactions with black patients. Most relevant to CVD is a study by Blair and colleagues 44 in which primary care providers' levels of implicit race bias predicted differences between black and white patients' reports of their clinicians' patient centeredness, with black patients reporting less patient centeredness for clinicians previously categorized as having higher levels of implicit racial bias. Numerous studies have investigated patients' perceptions of bias and discrimination while receiving health care.…”
Section: Race/ethnicity Racism and Cvdmentioning
confidence: 99%
“…Our study is the first to demonstrate that >70% of the participating cardiologists associated strength and risk taking with men more than women. Prior studies have shown that the majority of physicians have implicit race/ethnicity bias at rates similar to community samples 12, 46, 51, 52, 53. Physicians may be especially vulnerable to the use of implicit biases in clinical settings characterized by time pressure, brief encounters, and the need to manage very complex situations—the type of situations in which implicit bias is more likely to be applied 17, 50.…”
Section: Discussionmentioning
confidence: 99%